Tauhid Education in the Qur’an - Salman Al Farisi Lingga; Ahmad Mustaqim; Mohammmad Al Farabi; Ahmad Darlis (Solo Universal Journal of Islamic Education and Multiculturalism, 2023)
The type of research that the author uses is a type of qualitative research using a content analysis approach (Content Analysis), or what can be called a content study. This analysis is a research technique for making a conclusion or inference that can be replicated and the correctness of the data by considering the context. The object of this research is explored through various information in the form of books, interpretations, and journals. This journal aims to discuss humans who believe that Allah will become strong creatures in worship because worship is the result of monotheism, monotheism is the key to accepting all acts of worship so that they will produce noble humans, get instructions from Allah SWT to be blessed by Him so that included in the servant of Allah and entered into His heaven.